Association between distress tolerance and cannabis use disorder symptoms is stronger among U.S. young adults who identify as Hispanic and non-Hispanic Black - Jessica P. Orea; Haylee K. DeLuca Bishop; Kim Pulvers (Addictive Behaviors Reports)
Background: Young adults have the highest rates of Cannabis Use Disorder (CUD) among all age groups. One important yet understudied behavioral factor linked with CUD is Distress Tolerance (DT), and it is unknown whether this association varies as a function of race/ethnicity, despite health disparities. This study tests the hypothesis that the association between DT and CUD symptoms will be stronger among young adults who identify as non-Hispanic Black or Hispanic (under-represented minoritized; URM) and that cannabis coping motives will mediate this association. Method: Participants with past 30 day cannabis use (N = 451; M = 21.3 years; 54.8 % female; 33.0 % Hispanic; 35.7 % non-Hispanic Black) completed a cross-sectional survey administered through an online panel in 2021, which included measures of Distress Tolerance, Cannabis Coping Motives, and CUD symptoms. Moderation, mediation, and moderated mediation with covariates age, gender, education, income, and cannabis state legality were tested. Results: Greater distress intolerance was associated with higher CUD symptoms (b = 1.85, p = 0.000) and the effect was stronger for URM than NHW individuals (b = -2.43, p = 0.002).Cannabis motives mediated the association between distress intolerance and CUD symptoms (indirect effect: b = 1.069, SE = 0.222, 95 % CI(b) = [.662, 1.520]). Moderated mediation was not present, indicating that the link between DT and CUD symptoms by coping motives did not vary by race/ethnicity (index = 0.011, SE = 0.491, 95 % CI(b) = [-0.916, 1.033]). Conclusion: Developing DT may be a valuable approach for preventing and treating CUD, particularly among young adults from underrepresented backgrounds.